Urinary L-FABP and anaemia: distinct roles of urinary markers in type 2 diabetes - Eynatten, Maximilian von; Baumann, M.; Heemann, U.; Zdunek, D.; Hess, G.; Nawroth, Peter Paul; Bierhaus, Angelika; Humpert, Per Magnus (European journal of clinical investigation, 2010)
Urinary liver-type fatty acid binding protein (L-FABP) and kidney injury molecule (KIM)-1, novel urinary biomarkers of renal tubulointerstitial function, have previously been associated with acute ischaemic kidney injury. We studied the clinical significance of urinary L-FABP, KIM-1 and N-acetyl-β-glucosaminidase (NAG) as potential markers of renal function and chronic ischaemic injury in patients with diabetic nephropathy.
Gesehen am 13.09.2023